Pediatric Anti-N-Methyl-d-Aspartate Receptor Encephalitis: A Review with Pooled Analysis and Critical Care Emphasis - Remy, Kenneth E.; Custer, Jason W.; Cappell, Joshua; Foster, Cortney B.; Garber, Nan A.; Walker, L. Kyle; Simon, Liliana; Bagdure, Dayanand (Frontiers in Pediatrics, 2017)
Purpose: Anti N-methyl D-aspartate receptor encephalitis is being recognized with increasing frequency among children. Given the paucity of evidence to guide the critical care management of these complex patients, we provide a comprehensive review of the literature with pooled analysis of published case reports and case series. Methods: We performed a comprehensive literature search using PubMed, Scopus, EMBASE, and Web of Science for relevant published studies. The literature search was conducted using the terms NMDA, Anti-NMDA, Anti-NMDAR, pediatric encephalitis, and Anti-N-methyl-D-aspartate receptor, and included articles published between 2005 and May 01, 2016. Results: Forty-eight references met inclusion criteria accounting for 373 cases. For first-line treatments, 335 (89.8%) received high-dose corticosteroids, 296 received IVIG (79.3%), and 116 (31%) received therapeutic plasma exchange. In these, 187 children (50.1%) had a full recovery with only minor deficits, 174 patients (46.7%) had partial recovery with major deficits, and 12 children died. Additionally, 14 patients were reported to require mechanical ventilation. Conclusions: Anti-NMDA encephalitis is a formidable disease with great variation in clinical presentation and response to treatment. With early recognition of this second most common cause of pediatric encephalitis, a multi-disciplinary approach by physicians may provide earlier access to first and second-line therapies. Future studies are needed to examine the efficacy of these current therapeutic strategies on long-term morbidity.